Photothermal Janus anode with photosynthesis‐shielding effect for activating low‐temperature biological wastewater treatment - Zhang, Jingjing (2020)
Biological wastewater treatment (BWT), which is used to manage global wastewater, suffers from a sharp decrease in microbial activity at low temperature (<10 °C). Photothermal technology with a high energy efficiency theoretically exceeding 80% has the potential to activate low‐temperature BWT. However, photothermal BWT is threatened by the propagation of photosynthetic algae in wastewater under irradiation, and these microorganisms can suppress the functional bacteria or even kill anaerobic species by photosynthetically releasing oxygen. Herein, taking microbial fuel cells (MFCs) as a representative biological reactor, a photothermal Janus anode (PTJA) is designed, composed of a carbon black/polydimethylsiloxane photothermal nonporous layer and a graphite felt porous layer to promote low‐temperature BWT. Unlike traditional symmetrical porous anodes, the nonporous layer of the PTJA can isolate the wastewater in the porous layer from light irradiation during photothermal conversion, thus preventing photosynthetic algae from poisoning anaerobic functional microbes. Under ≈1 sun illumination, the PTJA MFC exhibits 1.6 and 24.2 times higher organic pollutant removal rate and power density generation, respectively, than MFCs using traditional anodes for low‐temperature BWT (7.0 ± 2.0 °C). This development can allow novel utilization of solar energy and is a promising resolution for low‐temperature BWT.